The Pass-on Effect of Tetracycline-Induced Honey Bee (Apis mellifera) Gut Community Dysbiosis - Jia, Shuo; Wu, Yuqi; Chen, Gongwen; Wang, Shuai; Hu, Fuliang; Zheng, Huoqing (Frontiers in Microbiology, 2022)
Gut microbial community plays an important role in the regulation of insect health. Studies on the western honey bee Apis mellifera suggest that antibiotic treatment greatly disrupt the native gut community, thereby harming host health. However, current studies mainly focus on the impact of direct exposure to antibiotic on individual bees, and little is known about the impact of social transmission of antibiotic-induced gut community disorder in honey bee colonies. In order to provide insight into the potential pass-on effect of antibiotic-induced dysbiosis, we colonized newly emerged germ-free workers with either normal or tetracycline-treated gut community and analyzed the gut bacteria composition. We also treated workers with low dosage of tetracycline to evaluate its impact on honey bee gut microbiota. Our results showed that the tetracycline-treated gut community caused disruption of gut community in their receivers, while the direct exposure to the low dosage of tetracycline had no significant effect. In addition, no significant difference was observed on the mortality rate of A. mellifera workers with different treatments. These results suggest that though the residue of antibiotic treatment may not have direct effect on honey bee gut community, the gut microbiota dysbiosis caused by high dosage of antibiotic treatment has a cascade effect on the gut community of the nestmates in honeybee colonies.